PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI LKPD INTERAKTIF BERBASIS LIVEWORKSHEETS DALAM PEMBELAJARAN ONLINE - Suharsono Suharsono; Sri Handayani (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
This study aims to increase students' motivation for learning during online learning during the pandemic. In addition, by increasing the motivation for learning, it is also expected to increase student learning outcomes through the use of interactive worksheets based on live worksheets. The subjects of this study were fourth grade students at SDN Kapasan V/147 Surabaya. This study uses quantitative and qualitative descriptive methods. The research instruments used include questionnaires, tests, and observations. In the first cycle, the result of teacher activity was 84%, while student activity was 72%, and for students' motivation for learning, it was 81%. In Cycle II, the results of the study increased, namely teacher activity increased to 90%, student activity increased to 88%, and student motivation for learning increased to 92%. From these results, it can be concluded that the use of interactive worksheets based on live worksheets can increase students' motivation for learning in online learning.